Field measurements of nitrogen fixation in leguminous trees used in agroforestry systems: influence of 15Nlabelling approaches and reference trees - Sanginga, N.; Danso, S.K.A.; Zapata, F. (Springer, 1996)
Appropriate 15N-labeling methods are crucial for estimating N2-fixation in trees used in agroforestry systems. A 4-year field experiment was conducted on an Alfisol in Southwestern Nigeria to compare the estimates of Na fixed in Leucaena leucocephala, using two non-N2-fixing leguminous trees, Senna siamea and S. spectabiIis, as reference plants and three different methods of introducing 15N into soil. The atom % 15N uptake pattern (as reflected in the leaves) was identical in both N2- and non-N2-fixing tree species irrespective of the 15N-application method. There was a significant decline in atom % 15N excess in the leaves of L. leucocephala (from 0.266 to 0.039), S. siamea (0.625 to 0.121), and S. spectabilis (from 0.683 to 0.118) from the first sampling 12 months after planting and the second sampling 18 months after sampling. From the second harvest in 1991 until the end of the experiment (fifth) harvest in 1993, however, the atom 15N % excess decline in leaves of the three species was less pronounced and depended on the method of 15N application. In these plants to which the tracer was applied once at planting, the 15N decline was steady between the second and the last prunings. In the split- application treatment, the atom 15N % excess increased slightly at the third pruning and decreased during the subsequent two prunings. The reference tree and the method of 15N application influenced the estimated proportion of N derived from atmospheric N2 by L. leucocephala, calculated as 73 and 64%, corresponding to 119 and 98 kg N ha-1 of N2 fixed per 6 months, when S. spectabilis and S. siamea were used as reference trees, respectively. The approach by which 15N- labeled fertilizer was applied to the soil in three splits gave slightly higher estimates of N derived from the atmosphere but this was of little agronomic significance because total N2 fixed was similar for all methods.